2019
DOI: 10.14716/ijtech.v10i1.1696
|View full text |Cite
|
Sign up to set email alerts
|

Review of Significant Maintenance Criteria for Tropical Green Roofs in Malaysia

Abstract: The implementation of green roofs on the top of buildings is becoming a trend in urban cities as they provide numerous benefits for green development growth. In Malaysia, numerous approaches towards sustainable development have been adopted in order to overcome crucial environmental issues such as urban heat islands, air pollution and lack of green spaces. One of the sustainable approaches that helps to minimize such problems is the use of vegetation or plant material on rooftops, also known as green roofs. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The type of covering material used for roof affects its ability to absorb or reflect heat. The study by (Algarni, Almutairi, and Alqahtani, 2022) showed that green roof with shallow-rooted grass lowered energy usage by 3.6% in six months (Shaharuddin, Khalil, and Saleh, 2019). Apart from the use of green roof, ceramic tiles and Ethylene Propylene Diene Terpolymer (EPDM) membranes can also serve as roofing material.…”
Section: Introductionmentioning
confidence: 99%
“…The type of covering material used for roof affects its ability to absorb or reflect heat. The study by (Algarni, Almutairi, and Alqahtani, 2022) showed that green roof with shallow-rooted grass lowered energy usage by 3.6% in six months (Shaharuddin, Khalil, and Saleh, 2019). Apart from the use of green roof, ceramic tiles and Ethylene Propylene Diene Terpolymer (EPDM) membranes can also serve as roofing material.…”
Section: Introductionmentioning
confidence: 99%